Amino acid substitutions involved in the adaptation of a novel H7N7 avian influenza virus in mice. (June 2020) - Wu, Haibo; Liu, Fumin; Yang, Fan; Xiao, Yixin; Yao, Hangping; Wu, Nanping
Abstract: The H7N7 avian influenza viruses can infect humans and poses a great threat to human health. To identify the amino acid substitutions that are associated with adaptation of avian-origin H7N7 virus to mammals, adaptation of the H7N7 virus was carried out by serial lung-to-lung passage in mice. Genomic analysis of the mouse-adapted virus revealed amino acid changes in the PB2 (E525G, M645I, and D701N), NP (I475V), HA(D103N), and NA(K142E) proteins. The adapted H7N7 virus was more virulent in mice than the wild-type virus. Our results suggest that continued surveillance of poultry populations for these substitutions in the H7N7 virus is required. Highlights: The adapted H7N7 avian influenza virus was more virulent in mice than the wild-type virus. Genomic analysis of the mouse-adapted H7N7 virus revealed amino acid changes in the PB2 (E525G, M645I, and D701N), NP (I475V), HA (D103N), and NA (K142E) proteins. Our results suggest that continued surveillance of poultry populations for these substitutions in the H7N7 virus is required.